Does a green supply chain improve corporate reputation? Empirical evidence from European manufacturing sectors. - Quintana-García, Cristina; Marchante-Lara, Macarena; Benavides-Chicón, Carlos Guillermo (Elsevier, 2021)
Managing supplier relationships in an environmentally responsible way may prevent risk of adverse publicity and reputational damage to the buying firm. Drawing on the stakeholder approach and the environmental management capability framework, the purpose of this paper is to gain further knowledge regarding the impact of strategies oriented to green supply chain management on a firm’s corporate reputation. We test a set of hypotheses in a panel data of European manufacturing companies for a period of ten years. Our findings provide strong support for the premise that supplier selection, monitoring and partnership termination based on environmental criteria positively influence corporate reputation. Additionally, evidence suggests that the implementation of those strategies in an integral way as well as progressing towards the adoption of green supply chain management benefit a firm’s reputation. This study has implications for theory and practice.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16941
Keywords: Logística empresarial - Aspectos ambientales; Productos manufacturados - Europa; Responsabilidad social de la empresa; Green supply chain; Corporate reputation; Stakeholders